IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI PEMBENTUK CITRA PERUSAHAAN DAN LOYALITAS - Mulyana .; Dian Ayuk Wulan Sari (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2013)
Implementation and disclosure of corporate social responsibility, or better known as corporate responsibility (CSR) started to emerge from three decades ago. Issue of CSR was due to a shift in paradigm where the company now not only aims to maximize profits but also are required to accommodate the needs of the community (society), its enviroments and stakeholders. In this study discusses the concept of three main dimensions of corporate social responsibility, namely benefit, people, and planet on the image of the company that fosters customer loyalty so dont move on product another (switching cost). Population in this recearh is buyer of KFC Semarangand know of CSR. The number of samples that used 96 responden, and technic sampling in this study were taken by using purposive sampling. The data obtained were analyzed by using PLS analysis technique (Partial Least Square). The result showed that the implementation CSR(benefit, people and planet) directly and positively related to company image and customer loyalty, company image has positive effect on customer loyalty and switching cost, furtheirmore switching cost to customer loyalty.Keywords : Corporate Social Responsibility, Image, Loyalty, Switching Cost.